2017
DOI: 10.1016/j.neuro.2016.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Developing and applying the adverse outcome pathway concept for understanding and predicting neurotoxicity

Abstract: The Adverse Outcome Pathway (AOP) concept has recently been proposed to support a paradigm shift in regulatory toxicology testing and risk assessment. This concept is similar to the Mode of Action (MOA), in that it describes a sequence of measurable key events triggered by a molecular initiating event in which a stressor interacts with a biological target. The resulting cascade of key events includes molecular, cellular, structural and functional changes in biological systems, resulting in a measurable adverse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(46 citation statements)
references
References 215 publications
(290 reference statements)
0
46
0
Order By: Relevance
“…Conversely these could be protective pathways, which the cell cannot activate upon a second exposure (point of no return; Krug et al 2014), or have reached a tipping point (Schildknecht et al 2017; Jennings et al 2004; Koppelstaetter et al 2004). Our results suggest new questions as to where the threshold of an effect lies (Bal-Price et al 2015, 2017a, b; Terron et al 2018). …”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Conversely these could be protective pathways, which the cell cannot activate upon a second exposure (point of no return; Krug et al 2014), or have reached a tipping point (Schildknecht et al 2017; Jennings et al 2004; Koppelstaetter et al 2004). Our results suggest new questions as to where the threshold of an effect lies (Bal-Price et al 2015, 2017a, b; Terron et al 2018). …”
Section: Discussionmentioning
confidence: 57%
“…Other reported early cellular events include mitochondrial dysfunction (decreased ATP production and decreased membrane potential), oxidative stress, impaired proteostasis, and accumulation of misfolded proteins (https://aopwiki.org/aops/3) (Bal-Price et al 2017a, b; Keane et al 2011; Terron et al 2018). Although dopaminergic degeneration has been studied extensively, recovery and adaptive mechanisms from toxicant exposure are rarely addressed.…”
Section: Introductionmentioning
confidence: 99%
“…These data suggest that the NeuroGlycoTest is able to detect specific effects on neurite glycosylation in the absence of general cytotoxicity and with higher sensitivity compared to neurite area measurements. This assay is therefore a useful novel addition to a battery of tests that are able to pick up alerts for potential neurotoxicants and modifiers of neural function (Bal-Price et al 2017;Gerhardt et al 2001;Hansson et al 2000;Hirt et al 2000;Ruszkiewicz et al 2018;Schultz et al 2015;Tiffany-Castiglioni et al 2006;Vassallo et al 2017;Zimmer et al 2011a, b). Based on the overall results of such a test battery, potential toxicants may be prioritized for further testing Li et al 2019;Schmidt et al 2017;Smirnova et al 2014;van Thriel et al 2012).…”
Section: Effect Of Mitochondrial Toxicants On the Neuroglycotest Readoutmentioning
confidence: 99%
“…Several studies have shown that EGCG can bind to laminin (Peter et al, 2017;Suzuki and Isemura, 2001) and disturb the adhesion of cells to the extracellular matrix (Bracke et al, 1987;Chen et al, 2003;Suzuki and Isemura, 2001) finally leading to an altered cell migration pattern (Bal-Price et al, 2017;Barenys et al, 2017a;Nyffeler et al, 2017). The structural moieties inducing this altered cell migration seemed to be galloyl/pyrogallol groups because in a previous study, catechins lacking these residues did not disrupt cell adhesion (Barenys et al, 2017a).…”
Section: Egcg ≈ G37 > M2 > M1 ≈ G56 > Nano-egcgmentioning
confidence: 90%